Revisiting Rheede’s ‘Katou-Indel’ and the discovery of a new species of Phoenix (Arecaceae) from India - Jacob, Joemon; Mohanan, Narayanan Nair; Kariyappa, K.c.; Kumar, Ettickal Sukumaran Santhosh; Suresh, S.; Hameed, Saheed S. (Phytotaxa, 2025)
The identity of Rheede’s ‘Katou-Indel’ is confirmed as Phoenix sylvestris, a species native to India (Kerala) and Sri Lanka. The names Phoenix pusilla, P. farinifera, and P. zeylanica are reduced to synonymy under P. sylvestris. The taxonomic circumscription of P. sylvestris is revised in this study, leading to the recognition of a new species, Phoenix roxburghii. The new species differs from P. sylvestris by its taller solitary trunk, larger leaves and leaflets, clustered acanthophylls musty-scented staminate flowers, micro-reticulate pollen, and larger obovoid orange-yellow fruits. A comprehensive description, along with photographs and relevant notes, is provided to aid in its identification.